Ubiquitin-independent proteasomal degradation during oncogenic viral infections - Hwang, Jiwon (2011)
Most eukaryotic proteins destined for imminent destruction are first tagged with a chain of ubiquitin molecules and are subsequently dismantled by the proteasome. Ubiquitin-independent degradation of substrates by the proteasome, however, also occurs. The number of documented proteasome-dependent, ubiquitin-independent degradation events remains relatively small but continues to grow. Proteins involved in oncogenesis and tumor suppression make up the majority of the known cases for this type of protein destruction. Provocatively, viruses with confirmed or suspected oncogenic properties are also prominent participants in the pantheon of ubiquitin-independent proteasomal degradation events. In this review, we identify and describe examples of proteasome-dependent, ubiquitin-independent protein degradation that occur during tumor virus infections, speculate why this type of protein destruction may be preferred during oncogenesis, and argue that this uncommon type of protein turnover represents a prime target for antiviral and anticancer therapeutics.